Design of Online Office Employee Attendance System on Website Based on HTML and CSS - Ramadhani, Fanny; Satria, Andy (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2024)
The continuous development of technology makes everything sophisticated and easy, such as attendance that can be accessed online. In this study, an online office employee attendance system was designed on an HTML and CSS-based website, where on this website there is a time and map that can show the whereabouts of employees and what time they are absent so that it is expected to prevent fraudulent attendance such as entrusting attendance. The purpose of this study is to help the office with attendance problems so that the office can easily control all employees in terms of attendance and all incoming data will be neatly arranged so that the data will be easy to summarize. This study uses a method of collecting data from observation as well as designing and building. So that with the observation method used, it can be used to find out and obtain data that will be used in the design and building stage of this website. This website itself is designed using the HTML programming language as the initial stage of the website page framework and uses the CSS programming language to make the layout of the website more attractive.